A REVIEW ON CHAOS AND ITS APPLICATIONS IN ECONOMICS - Saeed Moshiri (فصلنامه پژوهش‌های اقتصادی ایران, 2002)
Chaos theory is rather new in science, but, it is, in fact, rooted in ancients' perception of the world. The main idea is that although a complex system, such as world, seems to be generated by a random, and therefore, unpredictable process, it may run by a nonlinear deterministic process. Chaos theory has been applied to some Economic time series to see if they have an order, and, therefore, predictable. Some Economic time series, such as stock prices, look random, but, according to the chaos theory, they may come from a nonlinear deterministic process. If the data generating process is nonlinear, using traditional linear methods in estimation and forecasting can be misleading. Chaos theory is also applied to macroeconomic models. Some macroeconomic concepts, such as endogenous business cycles, can now be explained by the theory. In this paper, I try to review the chaos theory and its mathematical root for economists. Then, I will survey the Economic applications of the theory, and finally, will analyze different methods introduced for testing for chaos.